ISOLATION, IDENTIFICATION, AND ANTIBACTERIAL OF AMENTOFLAVONE FROM GARCINIA LATISSIMA MIQ. LEAVES - AMBARWATI, NENENG SITI SILFI; ELYA, BERNA; MALIK, AMARILA; HANAFI, MUHAMMAD; AWANG, MUHAMAD SHARUL NIZAM (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to isolate and identify the Bacillus subtilis antibacterial compound present in the leaves of the Garcinia latissima Miq. Methods: The extracts were obtained by maceration successively, and the active extract was fractionated by column chromatography. The isolation of the most active fraction was performed by open column chromatography and preparative thin-layer chromatography. The isolate antibacterial assay against Bacillus subtilis by microdilution method. The compound structure of the isolate was identified by the nuclear magnetic resonance method. Results: The most active extract of the extracts from Garcinia latissima Miq. leaves against Bacillus subtilis are the methanol extract. The most active fractions of the fractions from G. latissima Miq. Leaves methanolic extract was isolated. The active isolate was identified as Amentoflavone. Conclusion: G. latissima Miq. leaves had the potential to be used as antibacterial medicinal herbs and one of the isolates of G. latissima Miq. is amentoflavone (active against B. Subtilis).